Awareness of language: literacy and second language learning of Spanish in Mexico. Issue 6 (18th August 2019) - Chireac, Silvia-Maria; Francis, Norbert; McClure, John
ABSTRACT: This report presents findings from a follow-up exploratory study of the development of writing ability in an attempt to identify key component skills and competencies for elementary school literacy learners, grades 2nd, 4th and 6th. The first evaluation consisted in scoring first draft narrative texts for coherence, the second, an assessment of effective self-correction strategies. These two measures were compared to the results of a third test, of metalinguistic awareness related to children's ability to distinguish between the two languages that they know, and those of a fourth measure of orthographic knowledge. Participants were bilingual elementary school students from an indigenous community in Central Mexico. Results point to important opportunities in future research for the understanding of how metalinguistic awareness is related to literacy learning.